Green composites of natural fiber bamboo/pineapple leaf/coconut husk as hybrid materials - Suryani, .; Rihayat, Teuku; Nurhanifa, .; Siregar, J. P.; Jaafar, J.; Cionita, T.; Fitria, . (Institute of Physics Publishing, 2020)
Natural fiber reinforced polymer composite materials have been investigated for mechanical properties using by Universal Testing Machine (UTM) and structures of the fractured surfaces through optical and electron microscopy scanning with materials from natural fiber synthesis are bamboo fiber, pineapple leaf and coconut fiber mixed in polyester resin to be a hybrid composite material to see the best characteristics of tensile test properties. Mixing of natural fibers (filler) with polyester (matrix) has been developed as a renewable material. The results showed that the incorporation of bamboo-pineapple leaf-husk fiber have optimum tensile strength value 366 Mpa wirh flexural strength 0.302 Mpa. This is due to the presence of bamboo fiber has a high content of cellulose that can to replaced the failure in pineapple leafs and coconut fiber and make the hybrid composites not only as a strong material but biodegradable too.